Effects of foliar applications of Brassinolide and Selenium on the accumulation of Arsenic and Cadmium in rice grains and an assessment of their health risk. Issue 2 (28th January 2023) - Lan, Xiuquan; Li, Jiayuan; Chen, Jiancheng; Liu, Jing; Cao, Feishu; Liao, Changjun; Zhang, Zengyu; Gu, Minghua; Wei, Yanyan; Shen, Fangke; Wei, Xianghua; Luo, Xianbao; et al.
Abstract: Arsenic and cadmium pose a potential health risk to human beings via rice grain consumption. In the current study, a pot experiment was conducted to evaluate the effect of Br (5 mM and 20 mM) and Se (1 mM) at rice tillering and filling stages on Cd and As accumulation in rice grain and their health risk indices. The results showed that Br or Se applications at different stages of rice improved the photosynthesis, reduce MDA content in flag leaves by 17.41%–38.65%, increased rice biomass and grain yield by 10.50%–29.94% and 10.50%–36.56%, and enhanced grain N and P uptake by 3.25%–34.90%, and 22.98%-72.05%, respectively. Applications of Br and Se effectively decreased Cd and As concentration in rice grain by 31.74%–86.97% and 16.42%–81.13% respectively. Compared to the individual treatment, combined 20 mM Br and 1 mM Se at the filling stage showed the lowest accumulation of As (0.149 mg·kg −1 ) and Cd (0.105 mg·kg −1 ) in grain, and its health risk index was below the acceptable limits (HRI < 1). This implies that application of Br and Se at the filling stage is a promising strategy for the safe production of rice in As and Cd co-contaminated regions. NOVELTY STATEMENT: In this study, foliar applications of Br and Se at the grain filling and tillering stage demonstrate their effect on As and Cd accumulation. The findings showed that Br and Se resulted in the Se concentration in grains reaching the Se-enriched level, and the accumulation of As and Cd was the lowest. Furthermore, the application of Br and Se decreased lipid peroxidation, promoted N and P uptake, and increased the rate of photosynthesis in the rice plants, which resulted in increasing rice growth and grain yield. The HRI of heavy metals was below the acceptable limits after application of Br and Se.